ANALISIS FASILITAS ELEKTRONIK SURAT PEMBERITAHUAN (E-SPT) TERHADAP KEPATUHAN WAJIB PAJAK - Irwan Setiawan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Tax is the main element of state revenue, and national development is funded by taxes. Therefore, this research was conducted to see community participation in paying taxes. The research method uses quantitative with descriptive analysis approach and linear regression. The number of taxpayers used as respondents is 100 with a simple random sampling technique. The research instrument used a questionnaire with a Likert scale. The stages of the research consisted of descriptive analysis, validity test, reliability test, classic assumption test and hypothesis test. The results showed the tax facilities (E-SPT) affect the compliance of paying taxes. This finding suggests the role of community is very large towards tax revenue, but not all tax compliance, therefore, innovation is needed to make it easier to pay taxes